Advances in investment analysis and portfolio management - Lee, Cheng-Few. (Oxford, UK : Elsevier Science, 2002)
This annual research publication brings together investment analysis and portfolio theory and their implementation to portfolio management.
Includes bibliographical references.
oif 31/08/15
Loans
Keywords: Investment analysis; Portfolio management